Teaching mobile app creation for journalism students: a case study of android AppInventor in Brazil - Da Fontoura, Marcelo Crispim; Bisso Nunes, Ana Cecília; Campos Pellanda, Eduardo; Pase, André (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2017)
Due to the high demand for journalists that understand technology and embrace it as an important skillset in recent years, journalism schools have been adapting their curriculum to include those abilities in their classrooms. In this paper, we offer a case study of one such approach at PUCRS University in Brasil: from 2011 we have been challenging the students to make a journalistic app with Android AppInventor platform in the classroom. This paper addresses this experience and its perception of journalism and media students of PUCRS in Brazil.